The Successful Management of Non-healing Extraoral Draining Sinus of Odontogenic Origin: A Report of Two Cases - Soo, Eason; Ramlan, Nurul Ain; Khairulzan, Sarah Husna; Nordin, Rifqah; Rosli, Muhammad Syafiq Asyraf (Journal of Dentistry Indonesia, 2023)
Extraoral draining sinus of odontogenic origin usually lacks intraoral symptoms, thus it may be diagnosed as a cutaneous lesion. It is rare and may be confused with a wide variety of diseases for example furuncle, pericoronitis in relation to the mandibular third molars, parotid fistula, preauricular sinuses, periapical and periodontal pathology, and many more. Patients might seek treatment from their physician as they are not aware of its odontogenic origin and these cases usually are misdiagnosed and leading to inappropriate treatment. Objective: To discuss the detailed management of two cases of extraoral draining sinus that were successfully treated. Case Reports: The first case was referred by the Department of Oral and Maxillofacial Surgery, for management of extraoral draining sinus originating from tooth 36. In the second case, the extraoral draining sinus is caused by pulpal necrosis of several mandibular anterior teeth. Intra-radicular microorganisms in infected root canals primarily obligate anaerobes have been the aetiologic cause of apical periodontitis if left untreated may cause these types of symptoms. Conclusion: As it is uncommon and the absence of any dental symptoms, thus, it’s paramount important to diagnose these types of cases to treat the disease and to avoid unnecessary treatments such as prolonged prescription of antibiotics. Therefore, the dental cause should be ruled out for any cutaneous sinus tract so that a correct diagnosis can be ascertained, and proper management can be delivered to the patient.